Cleansing the cosmos : a biblical model for conceptualizing and counteracting evil - Warren, E. Janet (Eugene, Oregon : Pickwick Publications, 2012)
Adaptation of the author's Ph. D. thesis, University of Birmingham, 2012.
Keywords: Spiritual warfare; Good and evil -- Religious aspects -- Christianity; Metaphor -- Religious aspects -- Christianity